Acupressure mat-like nanostructure with improved SERS performance. (April 2022) - Li, Na; Hao, Zongshuo; Cao, Huiju; Guo, Liting; Cao, Hongwen; Li, Na; Yang, Yunfan; Jiao, Tifeng; Liu, Hailong; Wang, Mingli
Highlights: The solid ferro-nickel (NiFe) alloy was uniformly sputtered onto the cicada wing (CW) to make the substrate magnetic. The mass produced and dense silver nanoparticles (AgNPs) were pulled on NiFe film to further optimize the SESR substrate resulting in strong SERS signals with a sensitivity of 10 -15 M and EF of 4.69 × 10 4 . SERS activity of the optimized synthesized structure has been studied theoretically and experimentally. The results showed that the substrate remained magnetic property, polarization-independence, good reproducibility and time stability. The structure has practical application confirmed by the detection of illegally added melamine. Abstract: Bimetallic nanostructures have attracted much attention to prepare surface-enhanced Raman spectrometry (SERS) substrate. In this study, the problem that magnetic target material was difficult to glow in magnetron sputtering was overcome and the ferro-nickel (NiFe) alloy was uniformly sputtered onto the cicada wing (CW) to make the substrate magnetic. Then, the mass-produced and dense silver nanoparticles (AgNPs) were deposited on NiFe film to further optimize the SERS substrate by improving the method of oil–water interface self-assembly. It was worth mentioning that with the deposition of AgNPs, the SERS intensity was significantly enhanced, and the substrate remained magnetic property, polarization-independence, excellent sensitivity and reproducibility. We also calculated the Raman spectra of probe molecule bound to Ag10 clusters to theoretically verify the performance changes of the substrate observed from experiment. The fabricated SERS substrate not only showed excellent Raman performance, but also had grand application potential in food safety detection.